Heat stress enhances the accumulation of polyadenylated mitochondrial transcripts in Arabidopsis thaliana. - Alessio Adamo; John W Pinney; Andrea Kunova; David R Westhead; Peter Meyer (PLoS ONE, 2008)
Polyadenylation of RNA has a decisive influence on RNA stability. Depending on the organisms or subcellular compartment, it either enhances transcript stability or targets RNAs for degradation. In plant mitochondria, polyadenylation promotes RNA degradation, and polyadenylated mitochondrial transcripts are therefore widely considered to be rare and unstable. We followed up a surprising observation that a large number of mitochondrial transcripts are detectable in microarray experiments that used poly(A)-specific RNA probes, and that these transcript levels are significantly enhanced after heat treatment.As the Columbia genome contains a complete set of mitochondrial genes, we had to identify polymorphisms to differentiate between nuclear and mitochondrial copies of a mitochondrial transcript. We found that the affected transcripts were uncapped transcripts of mitochondrial origin, which were polyadenylated at multiple sites within their 3'region. Heat-induced enhancement of these transcripts was quickly restored during a short recovery period.Our results show that polyadenylated transcripts of mitochondrial origin are more stable than previously suggested, and that their steady-state levels can even be significantly enhanced under certain conditions. As many microarrays contain mitochondrial probes, due to the frequent transfer of mitochondrial genes into the genome, these effects need to be considered when interpreting microarray data.